Anthropogenically altered runoff processes in a waterlogged headwater catchment within the National Park Hunsrück-Hochwald, Germany - Zemke, Julian J. (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
This study is concerned with an initial investigation of anthropogenically altered runoff processes in a headwater catchment within the National Park Hunsrück-Hochwald (Germany) that is characterized by slope bogs and waterlogged soils. The examined area is crossed by a dense network of trenches, which were established in the course of forestry operations in order to utilize these waterlogged areas. An evaluation of the drainage network’s influence on runoff processes is attempted using water gauges and GIS-based analyses of the subcatchments. Results of the water year 2016 and a heavy rainfall event show that gauges in the study area react quickly to precipitation inputs and that water is retained only for a short time. The magnitude of runoff recession even in short dry spells permits the conclusion that the already merely residual slope bogs are endangered. The partial results of this study can serve as an instrument for rewetting actions as they allow spatially and temporally high resolved statements about the influence of drainage networks. Furthermore, this study is embedded in a long-term monitoring of hydrological processes and represents a first component of a detailed process-measurement taking place.